Molecular Aspects in Catalytic Materials for Pollution Elimination and Green Chemistry - Zhu, Junjiang (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Environmental issues have attracted great attention with the pursuit of a high quality of life, and the effective removal of environmental pollutants is a great challenge today. This includes two topics: one is to remove the pollutants produced post-treatment, and the other is to synthesize chemicals by a green route, avoiding producing pollutants in the process.Catalytic technology is an effective way to solve environmental problems, which can facilitate the conversion of pollutants to nontoxic or even useful chemicals. Thus, this reprint focuses on resolving the environmental problems by a catalysis technology, including photocatalysis, thermocatalysis, and electrocatalysis. Research works relating to the catalytic removal of pollutants or the catalytic synthesis of chemicals by a green route are reported.